QUALITY MANAGEMENT IN EDUCATION: A SYSTEMATIC APPROACH - Gafurova , Shahlokhon Karimovna (Educational Research in Universal Sciences, 2023)
The article describes the quality management of the educational institution; the existence of complementary approaches to the quality of education; practical, defining quality as the degree of conformity to goals (different consumer goals are different qualities that require quality management) and the second approach, organic, continuity refers to the first and internal processes that take place in the learning process.